THE SYNERGISTIC IMPACT OF DYNAMIC CAPABILITIES, EMPLOYEE SUSTAINABILITY PRACTICES, AND GREEN INNOVATION ON HUMAN CAPITAL RESILIENCE - Arif Sugiono; Ahmad Rifa'i; Supri Yanto (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study investigates the synergistic relationships between dynamic capabilities, employee sustainability practices, and green innovation in strengthening human capital resilience within Indonesia's emerging technology sector. A quantitative research design was employed, utilizing data from 42 technology companies listed on the Indonesia Stock Exchange. Primary data were collected through validated Likert-scale questionnaires measuring employee sustainability practices, while secondary data were obtained from the Central Statistics Agency, annual company reports, and the Global Innovation Index. Structural Equation Modeling using EViews software was applied to examine causal relationships and mediation effects. Results demonstrate that dynamic capabilities significantly influence human capital enhancement (β=0.32, p<0.01). Employee sustainability practices strengthen the relationship between green innovation and employee retention (R²=0.68). Green innovation serves as a partial mediator (VAF=45%) between sustainability practices and productivity. The study is limited to publicly listed companies, requiring future expansion to early-stage startups and longitudinal data collection for long-term effect analysis. This research represents the first empirical quantification of the synergistic impact of these three variables on human capital in Indonesia's technology sector, contributing novel insights to Resource-Based View theory and stakeholder theory within sustainability contexts.